Reconstruction of Caesarean Section Service Rates for National Health Insurance Patients - Regina, Vyola; Yurniwati; Adila Kasni Astiena (Community Medicine and Education Journal, 2024)
RSIA Permata Bunda as a JKN provider is paid according to the INA-CBG rate by BPJS Kesehatan, the amount of which does not match the costs incurred by the hospital so that there is a negative difference between the hospital section caesarea (SC) rate and the INA-CBG rate which reached 2 billion in 2021. The aim of this study was to reconstruct the SC service rate for JKN patients so that efficiency occurs. This study was an explanatory sequential mixed method design, preceded by quantitative research with unit cost calculation using the activity based costing (ABC) method and the average fee for service rate for hospital SC services and then qualitative research for interviews with informants. The unit cost calculated using the ABC method is lower than hospital package rates, fee for service rates but higher than INA-CBG rates for SC severity level I services in treatment classes I, II and III which causes losses for the hospital. Efficiency efforts that can be carried out by hospitals are through tariff reconstruction by adjusting LOS (length of stay), optimizing drug use and supporting examinations according to clinical pathways and changing the calculation of medical services from fee for service to a package system.